2021
DOI: 10.24272/j.issn.2095-8137.2021.079
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging reactive oxygen species is a potential strategy to protect <i>Larimichthys crocea</i> against environmental hypoxia by mitigating oxidative stress

Abstract: The large yellow croaker ( Larimichthys crocea ), which is an economically important mariculture fish in China, is often exposed to environmental hypoxia. Reactive oxygen species (ROS) homeostasis is essential for the maintenance of normal physiological conditions in an organism. Direct evidence that environmental hypoxia leads to ROS overproduction is scarce in marine fish. Furthermore, the sources of ROS overproduction in marine fish under hypoxic stress are poorly known. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Their safety and application stability need to be further explored. Luo et al, 2021 Lipoxygenase inhibitor O-phenanthroline 1. It has a certain inhibitory effect on the activity of lipoxygenase.…”
Section: Introduction To Oil Oxidationmentioning
confidence: 99%
“…Their safety and application stability need to be further explored. Luo et al, 2021 Lipoxygenase inhibitor O-phenanthroline 1. It has a certain inhibitory effect on the activity of lipoxygenase.…”
Section: Introduction To Oil Oxidationmentioning
confidence: 99%
“…Notably, out of 20 different oxidative products that have been characterized, 8-OHdG is considered the major element of oxidative DNA damage [43] . Numerous studies in recent years have analyzed levels of 8-OHdG in fish and shellfish DNA in relation to environmental pollutants, hypoxia, transport stress, as well as thermal stress [43] , [44] , [45] , [46] , [47] . For example, Gleason et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed the effects of the duration of hypoxia on oxidative stress, inflammation, and apoptosis, in aquatic organisms. For example, culturing large yellow croaker (Larimichthys crocea) in water with a DO level of 2 mg/L for 96 h can cause oxidative stress, affect the balance of the redox system, and lead to gill tissue damage [5]. A study on hybrid yellow catfish (Pelteobagrus fulvidraco ♀ × Pelteobagrus vachelli ♂) found that oxidative stress, respiratory metabolism, and apoptosis were affected when the DO level reached 0.7 ± 0.05 mg/L and was maintained at that level for 6.5 h [6].…”
Section: Introductionmentioning
confidence: 99%